Results of Study of Aggressiveness in Women with Depressive Disorder, History of Miscarrieage and Para-Suicide by Way of Intentional Non-Suicidal Self-Injury Using I-structural Test of Ammon (ISTA) - VodkaМ. (Psychiatry, Neurology and Medical Psychology, 2016)
Results of comparative study of characteristics of aggressiveness of 54 women with depressive disorders (F 32.0, F 32.1, F 33.0 according to ICD-10 criteria), history of miscarriage and fulfilled para-suicide by way of intentional non-suicidal self-injury(Х60-Х84 according to ICD-10 criteria) (1st clinical group), 30 women with depressive disorders, history of miscarriage and without signs of non-suicide (2nd clinical group) and 30 women with fulfilled reproductive function (history of one and more delivery at term with healthy children), without history of miscarriage, signs of mental disorders and self-injury (control group) were presented. Aggressiveness in comparison groups studied with the use of I-Structural Test of Ammon (Ich-Struktur Testnach Ammon, ISTA). The decreased values of constructive aggression were shown to distinguish patients with depression and history of miscarriage from mentally healthy women with successfully fulfilled reproductive function. Established that patients in the 1st group had significantly higher level of destructive and deficiency aggression comparing to patients from 2nd clinical group and control group. Increased destructive and deficiency aggression in women with depressive disorder, history of miscarriage and para-suicide is considered as individual psychotherapeutic aim in planning of treatment strategy.